AN INTRODUCTION TO THE HUMAN RIGTHS OF THE MEXICAN AGRICULTURE LABORERS - Gutierrez, Maribell (UNIVERSIDAD DE SONORA, 2022)
This article consists of showing the social situation in which vulnerable groups go through and as they are discriminated along our country, in this case agricultural workers, whose serious faults in the inherent individual rights, which are part of an International legislation for just over 70 years. Targeted actions by non-governmental groups have brought the population closer to the existing problems, first of all in order to help those most affected, helping them to improve their living conditions with the Red Nacional de Jornaleros and Jornaleros Agricolas  (REJJA) , since 2015 and local companies such as Sociedad Activa bringing education for life to the Sonoran agricultural fields. Actions like these could be called culturization, regional awareness or any other adjective that allows us to assess the importance of respect for human rights dignity in the Mexican fields whose products are served on our tables every day. Articles, official surveys, testimonies and data from reports on the subject were researched. It concludes with the interest of permeating current society and future generations, and continuing to generate information available to everyone that allows real knowledge of situations facing the most vulnerable Mexican groups. Keywords: Human rights, laborers, Mexican fields